2019
DOI: 10.1073/pnas.1906788116
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale analysis of task switching practice effects across the lifespan

Abstract: An important feature of human cognition is the ability to flexibly and efficiently adapt behavior in response to continuously changing contextual demands. We leverage a large-scale dataset from Lumosity, an online cognitive-training platform, to investigate how cognitive processes involved in cued switching between tasks are affected by level of task practice across the adult lifespan. We develop a computational account of task switching that specifies the temporal dynamics of activating task-relevant represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 36 publications
2
62
0
Order By: Relevance
“…We have made very few assumptions about the underlying cognitive mechanisms that produce a particular point on the reward-complexity curve. This contrasts with the modeling that was previously applied to the same data sets (Collins, 2018;Steyvers et al, 2019), which explored detailed mechanistic hypotheses. These different approaches have different advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…We have made very few assumptions about the underlying cognitive mechanisms that produce a particular point on the reward-complexity curve. This contrasts with the modeling that was previously applied to the same data sets (Collins, 2018;Steyvers et al, 2019), which explored detailed mechanistic hypotheses. These different approaches have different advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 93%
“…The second data set, reported in Steyvers et al (2019), consists of 1000 subjects playing the task-switching game "Ebb and flow" on the Lumosity platform ( Figure 1B). On each trial, subjects viewed moving leaves on a display and reported either the motion or pointing direction of the leaves.…”
Section: Data Setsmentioning
confidence: 99%
See 3 more Smart Citations